2020
DOI: 10.1038/s41598-020-77115-w
|View full text |Cite
|
Sign up to set email alerts
|

DCX+ neuronal progenitors contribute to new oligodendrocytes during remyelination in the hippocampus

Abstract: A pool of different types of neural progenitor cells resides in the adult hippocampus. Apart from doublecortin-expressing (DCX+) neuronal progenitor cells (NPCs), the hippocampal parenchyma also contains oligodendrocyte precursor cells (OPCs), which can differentiate into myelinating oligodendrocytes. It is not clear yet to what extent the functions of these different progenitor cell types overlap and how plastic these cells are in response to pathological processes. The aim of this study was to investigate wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 51 publications
1
16
0
Order By: Relevance
“…Although the effect of cuprizone treatment on hippocampal neurogenesis has not been extensively studied, our results agree with previous observations of reduced numbers of DCX+ cells in the cuprizone model (Abe et al, 2015). However, Klein et al found no significant differences in DCX+ cells after 1 or 2 wks remyelination but determined that DCX-expressing neural progenitors can contribute to the mature oligodendrocyte pool (Klein et al, 2020). The observation of increased OPC NG-2+ in hCX3CR1 I249/M280 mice point to an unexplored area regarding the use of FKN as an effective mediator for the interaction of new neurons and oligodendrocytes to enhance remyelination and repair.…”
Section: Discussionsupporting
confidence: 91%
“…Although the effect of cuprizone treatment on hippocampal neurogenesis has not been extensively studied, our results agree with previous observations of reduced numbers of DCX+ cells in the cuprizone model (Abe et al, 2015). However, Klein et al found no significant differences in DCX+ cells after 1 or 2 wks remyelination but determined that DCX-expressing neural progenitors can contribute to the mature oligodendrocyte pool (Klein et al, 2020). The observation of increased OPC NG-2+ in hCX3CR1 I249/M280 mice point to an unexplored area regarding the use of FKN as an effective mediator for the interaction of new neurons and oligodendrocytes to enhance remyelination and repair.…”
Section: Discussionsupporting
confidence: 91%
“…Ptpru —a member of the R2B PTP family—regulates tyrosine phosphorylation and cadherin-based cell adhesion, and was found to be involved in CNS development [ 108 , 112 ]. Ptpru regulates neurite extension by inactivating β-catenin—a player in the Wnt signaling pathway [ 111 , 145 , 146 ]. The Wnt/β-catenin signaling pathway is a prominent regulator of differentiation of OPCs into mOLs [ 139 , 147 , 148 ].…”
Section: Discussionmentioning
confidence: 99%
“…This conjecture is consistent with the elevated anxiety levels we previously observed in NexKO mice compared to controls [ 56 ]. Moreover, it was recently shown that Dcx -enriched neuronal precursor cells are able to differentiate into mOLs in the murine hippocampus when demyelination is induced [ 146 ]. As was shown here and in previous studies, myelin and OL differentiation properties are aberrated in the brains of NexKO mice compared to controls [ 34 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Classic neurodevelopmental hierarchical model in which neural stem cells give rise to gradually more restricted progeny including neurons, oligodendrocytes and astrocytes. Emerging evidence has demonstrated additional complexity and plasticity within this hierarchical organization [114,115].…”
Section: Discussionmentioning
confidence: 99%